Implementation STEAM and Thematic Learning Models Assisted by STEMATIK Learning Media in Elementary School - Atika Azzahro Hazima; Eko Prasetyo; Aulia Hanif Annisa; Ranti Maryanti (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2024)
The aim of this research was to explain the component analysis of integrating STEAM and thematic learning using STEMATIK learning media, to describe the importance of using learning media in enhancing students’ independence and motivation to learn, and to present the results of using STEMATIK learning media as a tool for learning mathematics. The research method employed was a quasi-experiment. This study tested causal results to determine the influence of one variable on another. The product development process was based on the ADDIE model, which is a systematic approach that includes five different stages: analysis, design, development, implementation, and evaluation. The method used in this research was the descriptive, qualitative and quantitative method. The research results showed an increase in students’ independence and learning outcomes. The use of learning media can increase student activity in the classroom, thereby creating a conducive classroom condition.